Development of the Pot Artistry Game to Stimulate Fine Motor Skills in Children Aged 5-6 Years - Al-Haq, Opie Faradika Avilian Imani; Pramono, Pramono; Tirtaningsih, Munaisra Tri; Putra, Yudithia Dian (Universitas Negeri Malang, 2024)
This research aims to develop an educational toy to stimulate fine motor skills in children aged 5-6 years, responding to the lack of such tools in several educational institutions. Referring to the Regulation of the Minister of Education & Culture Number 137 of 2014 on National Standards for Early Childhood Education, specifically the Fine Motor Indicators for ages 5-6 years, researchers designed the